Energy efficiency and environmental innovations in locomotive traction: optimization of driving modes based on real operating data - Samiliak, Serhii (Global Prosperity, 2025)
Abstract. The article presents the development and experimental verification of energy-saving locomotive control methods based on the analysis of 2,840 actual trips with a total mileage of 403,000 kilometers. The research was conducted using data on the operation of freight trains on the Kovel--Sarny section of the Lviv Railway during 2022--2024, using DE1 series DC electric locomotives, 2TE116 diesel locomotives, and TGM6G hybrid locomotives. Based on the processing of 2,840 trips with a total mileage of 403,000 kilometers, mathematical models of energy consumption for different types of traction rolling stock were constructed, taking into account the track profile, train weight, weather conditions, and the driver's driving style. An algorithm for optimizing traction and coasting modes was developed, which reduces electricity consumption by 12.4% for electric traction and diesel fuel consumption by 8.7% for diesel traction compared to traditional train operation. Experimental testing on a 142 km route with 47 drivers showed that the implementation of the recommendation system allows for an average reduction in energy consumption of 11.8% without compromising schedule adherence.A comparative analysis of the efficiency of different types of traction has shown that electric locomotives with regenerative braking return 18-24% of the energy consumed to the grid on sections with a complex profile, while hybrid diesel locomotives show fuel savings of up to 15% compared to traditional diesel-electric locomotives in shunting operations. It has been calculated that large-scale implementation of the proposed methods on the Ukrzaliznytsia network could reduce CO₂ emissions by 340-420 thousand tons annually and generate an economic effect of about 2.8 billion hryvnia by reducing fuel and energy costs.